Influence of local institutional profile on global value chain participation: An emerging market perspective. Issue 3 (13th February 2020) - Hong, Jin; Zhou, Chongyang; Wang, Ruicheng
Abstract : Purpose: The emergence and rapid expansion of global value chains (GVCs) have profoundly changed and reshaped the global trade regime. Although many determinants of GVC participation of enterprises have been discussed extensively in extant literature, the important influence of local institutional profile on GVC participation is often neglected. The purpose of this paper is to investigate the influence of local institutional profile on GVC participation. Design/methodology/approach: Taking the World Bank Enterprise Survey as the empirical sample, it is used an econometric method (propensity score matching technique) to test the relationship between local institutional profile and GVC participation. Findings: Local institutional quality is positively related to GVC participation. Moreover, GVC participants display better innovation performance than non-participants. Innovation benefit from GVC participation is contingent upon the abilities of the participants, namely, absorptive capacity and research and development collaboration experience. GVC participants who only either export or import is compared with those who export and import; the findings show that the latter benefits more than the former. Originality/value: This study offers researchers and practitioners a detailed view of local institutional profile and GVC participation.